Liquid substrates for mass production of potent biocontrol agents of water hyacinth - A. NASEEMA, R. PRAVEENA * and (Indian Phytopathology, 2008)
Ground nut oil cake extract recorded maximum mycelial weight of F. pallidoroseum, F. equiseti and C. gloeosporioides but sporulation and spore viability was less, when compared with other substrates. Coconut water and jaggery water supported maximum sporulation and retained the spore viability for a period of one month.